Signal representation and processing of nucleotide sequences. (24th November 2008) - Cristea, Paul; Tuduce, Rodica; Nastac, Iulian; Cornelis, Jan; Deklerck, Rudi; Andrei, Marius
Sets of related signals can be represented by separating their joint variation and showing the individual signal offsets with respect to this reference. An example is the Genomic Signal Analysis (GSA) of pathogen variability. The conversion of symbolic nucleotide sequences to genomic signals allows to use signal processing methods to analyse genomic data. This approach reveals striking regularities in the distribution of nucleotides and pair of nucleotides along the sequences, in both prokaryotes and eukaryotes. Genomic signals can also be used for sequence prediction, similarly to time series prediction. The methodology is also adequate for studying the development of pathogen multiple resistance to drugs.